Particle analysis of shape factors according to American Society for testing and materials - Schröder, Stefan; Braun, Steffen; Müller, Ulrike; Sonntag, Robert; Jäger, Sebastian; Kretzer, Jan Philippe (Journal of biomedical materials research. Part B, Applied biomaterials, 2020)
Polyethylene wear is one of the major factors influencing the survivorship of joint replacements. Depending on the number, size and morphology of the polyethylene particles, biological responses of the periprosthetic soft tissue in terms of inflammatory processes can occur, leading to loosening of the implant. Various parameters are used to analyze wear particles, which are usually determined by examining scanning electron microscopy (SEM) images with a particle analysis program. In this study, three different software solutions for particle analysis (self-developed Particleanalyzer_HD, Leica QWin and ImageJ) were compared regarding particle number, size and morphology. These solutions were also compared to the American Society for Testing and Materials (ASTM) F1877-16 specifications regarding particle morphology. SEM image analysis revealed no differences for the equivalent circle diameter (p = 0.969). However, a significant difference was found for the aspect ratio between the Particleanalyzer_HD and the other two software solutions (p < 0.001) and between Leica QWin and the other two software solutions regarding the roundness (p < 0.001). Only the Particleanalyzer_HD showed an excellent agreement with the ASTM standard for both morphology parameters (intraclass correlation = 1.000). Only the Particleanalyzer_HD calculated the two morphology parameters according to the ASTM standard. A comparison of the particle morphology between different studies is barely possible, as different algorithms for particle analysis are used. It is strongly recommended that the calculation according to the ASTM standard is used to improve future comparability of findings from wear analysis studies. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 108B:225-233, 2020.